High-pressure mechanistic insight into bioinorganic no chemistry - Orzeł, Łukasz; Oszajca, Maria; Polaczek, Justyna; Porębska, Dominika; Eldik, Rudi van; Stochel, Grażyna (Molecules, 2021)
Pressure is one of the most important parameters controlling the kinetics of chemical reactions. The ability to combine high-pressure techniques with time-resolved spectroscopy has provided a powerful tool in the study of reaction mechanisms. This review is focused on the supporting role of high-pressure kinetic and spectroscopic methods in the exploration of nitric oxide bioinorganic chemistry. Nitric oxide and other reactive nitrogen species (RNS) are important biological mediators involved in both physiological and pathological processes. Understanding molecular mechanisms of their interactions with redox-active metal/non-metal centers in biological targets, such as cofactors, prosthetic groups, and proteins, is crucial for the improved therapy of various diseases. The present review is an attempt to demonstrate how the application of highpressure kinetic and spectroscopic methods can add additional information, thus enabling the mechanistic interpretation of various NO bioinorganic reactions.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Cobalamins; Heme proteins; High-pressure techniques; Iron complexes; Kinetics; Nitric oxide; Porphyrins